Morphometric characteristics of lumbar vertebral pedicles in Mexican population. Implications for transpedicular lumbar fusion surgery - Castro Reyes, César Daryl; Vidal Torres, Oscar; Camara Lemarroy, Carlos Rodrigo; Aguirre, P. O. M.; Salinas Zertuche, A.; De la Garza Castro, Oscar; Vílchez Cavazos, José Félix; Morales Avalos, Rodolfo; Elizondo Omaña, Rodrigo Enrique; Guzmán López, Santos (2015)
Introduction. Spinal fusion surgery using transpedicular fixation is the most common technique for surgical treatment of spinal pathologies of any etiology. The morphometric characteristics of the vertebral pedicle determine the size and shape of pedicle implants. The objective of this study is to determine the morphometric characteristics of the lumbar vertebral pedicle in Mexican population by direct measurement of bone parts. Materials and Methods. We analyzed 65 L1–L5 cadaver lumbar spines from a collection of bone specimens from the Department of Human Anatomy. Pedicle width, height, and length were determined bilaterally in each sample studied. We obtained measures of central tendency, and parametric correlation tests were performed with a 95% confidence interval to determine if significant differences exist between the lumbar vertebral levels. Results. Pedicle width increased from L1 to L5. We obtained a minimum mean value of 7.40 ± 1.84 mm at L1 and a maximum mean value of 14.74 ± 3.77 mm at L5. Pedicle height decreased from L1 to L4 with a subsequent increase at L5. We obtained a maximum mean value of 18.32 ± 4.15 mm at L5 and minimum mean value of 14.09 mm ± 2.75 at L4. Significant differences were observed (P < 0.05) when groups were compared. Conclusions. This study accurately describes the morphometric characteristics of the lumbar vertebral pedicle. These data will be useful for correct selection and positioning of transpedicular screws.